Catatonia in Older Adult Individuals with Intellectual Disabilities - White, Megan; Maxwell, Edward; Milteer, Warren E.; de Leon, Jose (Case Reports in Psychiatry, 2015)
Catatonia has been described in children with intellectual disabilities (IDs). These are the first three published cases of catatonia in adults older than 50 years of age with IDs. They were followed using the KANNER scale and, in one case, creatinine phosphokinase (CPK) monitoring. Case 1 is a 67-year-old Caucasian who probably had been having intermittent episodes of undiagnosed catatonia withdrawal for many years. His episodes of agitation and withdrawal behavior responded to lorazepam up to 8 mg/day. Case 2 is a 63-year-old Caucasian male who had probably had undiagnosed catatonic episodes since age 25. An agitation episode that rated 88 on Part 2 of the KANNER scale ended within minutes after he received 1 mg of intramuscular lorazepam. He had no symptom relapses for 4 years after getting stable oral lorazepam doses (3–8.5 mg/day). Case 3 is a 55-year-old African-American male with severe ID and bradycardia (with a pacemaker). He had been “institutionalized” since age 22 and his undiagnosed catatonic episodes appeared to have been intermittently present for at least the last ten years. As he became tolerant and experienced symptom relapse, oral lorazepam was slowly increased (1.5–18 mg/day). Electroconvulsive therapy was ruled out due to his pacemaker.